Maturity onset diabetes of the young in India – a distinctive mutation pattern identified through targeted next‐generation sequencing. (7th August 2014) - Chapla, Aaron; Mruthyunjaya, Mahesh Doddabelavangala; Asha, Hesarghatta Shyamasunder; Varghese, Denny; Varshney, Manika; Vasan, Senthil K.; Venkatesan, Padmanaban; Nair, Veena; Mathai, Sarah; Paul, Thomas Vizhalil; Thomas, Nihal
Summary Objective To establish and utilize a Next‐Generation Sequencing (NGS)‐based strategy to screen for maturity onset diabetes of the young (MODY) gene mutations in subjects with early‐onset diabetes. Patients and Methods Maturity onset diabetes of the young (MODY) genetic testing was carried out in 80 subjects of Asian Indian origin with young onset diabetes to identify mutations in a comprehensive panel of ten MODY genes. A novel multiplex polymerase chain reaction (PCR)‐based target enrichment was established, followed by NGS on the Ion Torrent Personal Genome Machine (PGM). All the mutations and rare variants were confirmed by Sanger sequencing. Results We identified mutations in 11 (19%) of the 56 clinically diagnosed MODY subjects and seven of these mutations were novel. The identified mutations include p.H241Q, p.E59Q, c.‐162G>A 5′ UTR in NEUROD1, p.V169I cosegregating with c.493‐4G>A and c.493‐20C>T, p.E271K in HNF4A, p.A501S in HNF1A, p.E440X in GCK, p.V177M in PDX1, p.L92F in HNF1B and p.R31L in PAX4 genes. Interestingly, two patients with NEUROD1 mutation were also positive for the p.E224K mutation in PDX1 gene. These patients with coexisting NEUROD1–PDX1 mutations showed a marked reduction in glucose‐induced insulin secretion. All 24 subjects who had not met the clinical criteria of MODY were negative for the mutations. To the best of our knowledge, this is the first report of PDX1, HNF1B, NEUROD1 and PAX4 mutations from India. Conclusions Multiplex PCR coupled with NGS provides a rapid, cost‐effective and accurate method for comprehensive parallelized genetic testing of MODY. When compared to earlier reports, we have identified a higher frequency and a novel digenic mutation pattern involving NEUROD1 and PDX1 genes.